Pengaruh Kebijakan Pemerintah terhadap Pendapatan Petani Tembakau di Desa Batu Nampar - Muhamad Zaril Gapari (MANAZHIM, 2023)
The agricultural sector is a large enough contributor and can last a long time in facing monetary turmoil because it is the basis of life for the people of NTB in general and East Lombok in particular. The agricultural sector is still the main livelihood for most of the population of East Lombok. The agricultural sector in a broad sense is an important and strategic sector in West Nusa Tenggara (NTB). The most developed agribusiness activity on the island of Lombok is tobacco farming. This study aims to determine the effect of government policies on the income of tobacco farmers in Batu Napar Village, Jerowaru District. The type of research used is quantitative descriptive research. The research population was 296 and the research sample was 38 people. The data collection techniques used were observation, interviews and documentation. Sources of data used are primary data and secondary data. The data analysis technique used is income analysis, simple linear regression analysis, data normality test, and t test as a hypothesis test. Based on the results of the income analysis, it shows that the average income of tobacco farmers is Rp. 94,842,105 per harvest, so it can be said that this government policy has a considerable impact on increasing the income of tobacco farmers. The results of the hypothesis test with the t test show t count = 6.054 > t table = 2.797 so that Ha is accepted and Ho is rejected. With the regression direction Y = 14.5 + 2.8X. This shows that there is an influence between government policies on the income of tobacco farmers in Batu Napar Village, Jerowaru District.